Morphological expression of the pig coronary sinus and its tributaries: A comparative analysis with the human heart (2015)
The objective of this study was to determine the morphological expression of the coronary sinus and its tributary branches in pigs. This descriptive cross-over study evaluated continuous variables with t test, and discrete variables with the Pearson.